2010
DOI: 10.1007/s00296-010-1684-y
|View full text |Cite
|
Sign up to set email alerts
|

Malignancies associated with systemic lupus erythematosus in Taiwan: a nationwide population-based cohort study

Abstract: Patients with systemic lupus erythematosus (SLE) are suggestive to have a higher cancer risk. The aim of this study is to evaluate the possible association of malignancy and SLE in Taiwan. We used the data of the National Health Insurance system of Taiwan to assess this issue. The SLE cohort contained 2,150 patients, and each patient was randomly frequency matched to 8 people without SLE on age and sex. The Cox's proportion hazard regression analysis was conducted to estimate the effects of SLE on the cancer r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…The SLE mortality risk estimate for surgical hospitalisation is lower than that for all-cause hospitalisation 21. Our result showed a high proportion of men among the patients with SLE, an intriguing fact consistent with previous cohort studies in Taiwan 22 23. Similar to the concurrence of rheumatoid arthritis and SLE reported in an Australian case series,24 an increased prevalence of rheumatoid arthritis was found among our lupus patients.…”
Section: Discussionsupporting
confidence: 92%
“…The SLE mortality risk estimate for surgical hospitalisation is lower than that for all-cause hospitalisation 21. Our result showed a high proportion of men among the patients with SLE, an intriguing fact consistent with previous cohort studies in Taiwan 22 23. Similar to the concurrence of rheumatoid arthritis and SLE reported in an Australian case series,24 an increased prevalence of rheumatoid arthritis was found among our lupus patients.…”
Section: Discussionsupporting
confidence: 92%
“…Our research team previously used the NHIRD to evaluate the risk of malignancy for patients with systemic lupus erythematosus (SLE). We found that Taiwanese patients with SLE have a marginally significantly higher overall risk of developing cancer (24). These results motivated us to explore the possible association between other immune-mediated disorders and cancer.…”
Section: Discussionmentioning
confidence: 96%
“…Compared with enrollees with a minor psychiatric disorder, those with a major psychiatric disorder have a higher use and a greater cost of mental health care services [14]. Based on the NHI data and the catastrophic illness register data, the co-morbidity of malignancy with other diseases listed as catastrophic illnesses has also been studied in Taiwan [15-17]. Furthermore, many Taiwanese cancer patients could potentially benefit from hospice care; the rate of hospice utilization during their final year of life was calculated, and was shown to have grown substantially from 5.5% to 15.4% from 2000 to 2004 [18].…”
Section: Discussionmentioning
confidence: 99%